Nationalist Ethnicities as Religious Identities - Imtiyaz Yusuf (International Institute of Islamic Thought, 2017)
For centuries, the Rohingya have been living within the borders of the country established in 1948 as Burma/Myanmar. Today left stateless, having been gradually stripped of their citizenship rights, they are described by the United Nations as one of the most persecuted minorities in the world. In order to understand the complexity of this conflict, one must consider how Burma is politically transitioning from military to democratic rule, a process that is open (much as was Afghanistan) to competition for resources by international and regional players such as the United States, China, India, Israel, Japan, and Australia.1 To be fair, the record of Southeast Asian Muslim countries with Buddhist minorities is also not outstanding. Buddhist minorities identified as ethnic groups have faced great discrimination in, among others, Bangladesh, Malaysia, Indonesia, and Brunei ...